Trichoscopic Patterns of Scalp Dermatoses: An Observational Cross-sectional Study - G Sukanya; NR Vignesh; C Geo Danny; Sane Roja Renuka (Journal of Clinical and Diagnostic Research, 2023)
Introduction: Trichoscopy is a well-acclaimed diagnostic tool for numerous dermatoses. Scalp disorders contribute to a significant percentage of daily visits to the outpatient dermatology department, and a multitude of trichoscopic signs have been documented in the literature. The consistency and repeatability of these signs add weight to their diagnostic value. Aim: To determine the various trichoscopic patterns observed in classical cases of scalp dermatoses and to differentiate between different scalp disorders. Materials and Methods: The present observational crosssectional study included 100 newly diagnosed cases of scalp dermatoses attending the Dermatology Outpatient Department at Sree Balaji Medical College and Hospital, Chennai, India. The study was conducted over a period of six months (180 days) from December 2021 to May 2022. After obtaining a thorough history and conducting clinical examinations, patients underwent trichoscopy. Photographs were taken, and the data obtained were systematically tabulated. The scalp disorders studied included Androgenetic Alopecia (AGA), Alopecia Areata (AA), Telogen Effluvium, Tinea Capitis, Trichotillomania (TTM), Seborrhoeic Dermatitis, Scalp Psoriasis, Discoid Lupus Erythematosus (DLE), Lichen Plano-Pilaris (LPP), and scalp verruca. All data were entered into Microsoft excel and analysed using Statistical Package for Social Sciences software. Results: Trichoscopic findings from the 100 cases were categorised and tabulated according to pattern and condition for better understanding and comparison. Trichoscopic patterns observed were categorised as dots, vessels, shaft patterns, and changes in the inter and perifollicular areas. Out of the 100 patients, 67 presented primarily with alopecia, of which 56 patients (83.5%) had non scarring alopecia and 11 patients (16.4%) had scarring alopecia. The highest number of cases was observed in alopecia areata (n=20), where exclamation mark hairs were seen in all individuals, followed by coudability sign, yellow dots, and black dots. Among the androgenetic alopecia cases (n=18), anisotrichosis, pearly white dots, yellow dots, and an increased vellus-to-terminal hair ratio were observed in 100% of cases. Conclusion: While certain signs/findings are specific, most trichoscopic patterns overlap in various skin conditions. Therefore, dermatologists should be aware of the patterns observed in trichoscopy and the need to stay updated with the latest findings.